The Evolution, Hotspots, and Trends in Research on Facilities of Combined Medical and Nursing Care for the Elderly - Zhe Chen; Qiang Yao; Na An (Buildings, 2022)
With the significant increase in global ageing and its derivative risks, governments and academic communities have been widely concerned with research on facilities of combined medical and nursing care for the elderly (FCMNCE). Using Citespace and VOSviewer bibliometric software, in this paper, we explore the evolutionary phases, hotspots, and trends in research on FCMNCE. First, the concept and connotation of FCMNCE are clarified. Secondly, based on a bibliometric analysis of the number of annual publications, disciplinary distribution, publication sources, and country distribution, we classify research on FCMNCE into four phases: the exploratory phase of influencing factors, the constructive phase of combined medical and nursing care patterns, the improvement phase of life quality, and the synergistic development phase of science and technology. Thirdly, based on a bibliometric analysis of keyword clustering, annual overlap, and burst keywords, the research hotspots of FCMNCE are identified. Finally, we predicts that future research on FCMNCE will be characterized by the trends of smart elderly facilities, smart medical services, and public health risks. Our conclusion can help researchers to understand the research status and development trends of FCMNCE and select future research directions based on their disciplinary background.